Dampak Pandemi Covid-19 pada Kelayakan Usaha Perikanan Rajungan di Teluk Banten - Vianka Nafisa Salsabila; Muta Ali Khalifa; Adi Susanto (Institut Pertanian Bogor, 2022)
The Archipelagic Fishing Port of Karangantu located in Banten Bay is one of the blue swimming crab fishing centers in the Java Sea. Covid-19 pandemic had significant effect on blue swimming crab fisheries in Karangantu, especially on the increasing of fishing operational cost, decreasing of price, and limited acces for market distribution. This study aims to analyse the feasibility of blue swimming crab fisheries activity using bottom gillnet in Banten Bay after Covid-19 pandemic. The research was conducted in May-June 2021 in Karangmulya Village, Kasemen District, Serang City with a total of 22 respondents. The data were collected using deep interview with each respondent who was selected purposively. The analysis of business feasibility was conducted based on the parameters of the ratio between income and costs (R/C), payback period (PP), and net present value (NPV). The results show the Covid-19 induced the decreasing of R/C ratio value from 2.08 before to 1.81 after Covid-19 pandemic, respectively. The value of PP also increased from 0.65 years to 0.68 years. Moreover, the potential profit of blue swimming crab fishing also decreased from IDR 55 million before Covid-19 to IDR 52 million after Covid-19 pandemic. However, due to the positive NPN value, the blue swimming crabs fishing actvity using bottom gill nets in Banten Bay is still feasible to be developed. Keywords: blue swimming crab, Covid-19, impact, fisheries